Assessment of The Nurses’ Knowledge about Skin Care For Patients Undergo Radiotherapy of Breast Cancer at Al–Amal National Hospital for Cancer Management in Baghdad City - Wafaa M. A. Al-Attar (Kufa Journal for Nursing Sciences)
Objectives: The study aims to identify the nurses knowledge toward skin care for patients undergo radiotherapy breast cancer